Joule-Thomson Expansion of the Quasitopological Black Holes - Mirza, Behrouz; Naeimipour, Fatemeh; Tavakoli, Masoumeh (Frontiers in Physics, 2021)
In this paper, we investigate the thermal stability and Joule-Thomson expansion of some new qusitopological black hole solutions. We first study the higher-dimensional static quasitopological black hole solutions in the presence of Born-Infeld, exponential and logarithmic nonlinear electrodynamics. The stable regions of these solutions are independent of the types of the nonlinear electrodynamics. The solutions with the horizons relating to the positive constant curvature, k=+1, have a larger region in thermal stability, if we choose positive quasitopological coefficients, μ_i>0. We also have a review on the power Maxwell quasitopological black hole. Then, we obtain the five-dimensional Yang-Mills quasitopological black hole solution and compare with the quasitopological Maxwell solution. For large values of the electric charge, q, and the Yang-Mills charge, e, we showed that the stable range of the Maxwell quasitopological black hole is larger than the Yang-Mills one. This is while thermal stability for small charges has the same behavior for these black holes. In the following, we obtain the thermodynamic quantities for these solutions and then study the Joule-Thomson expansion. %We can investigate We consider the temperature changes in an isenthalpy process during this expansion. The obtained results show that the inversion curves can divide the isenthalpic ones into two parts in the inversion pressure, P_i. For P